Experimental investigation of the behaviour of concrete beams reinforced with GFRP bars under static and impact loading. (15th April 2016) - Goldston, M.; Remennikov, A.; Sheikh, M. Neaz
Highlights: Flexural behaviour of GFRP RC beams has been investigated. Effects of concrete strength and reinforcement ratio have been investigated. Failure modes of GFRP RC beams under static and impact loading are identified. Dynamic moment capacities showed 15–20% increase compared to static moment capacities. Abstract: Composite materials, including Fibre Reinforced Polymer (FRP) bars, have been gaining momentum as alternatives to traditional steel reinforcements in civil and structural engineering sectors. FRP materials are non-corrosive, non-conductive, and lightweight and possess high longitudinal tensile strength, which are advantageous for their use in civil infrastructure. This paper presents the results of an experimental investigation into the effects of the use of glass FRP (GFRP) bars as internal reinforcement on the behaviour of concrete beams. Both static and dynamic (impact) behaviours of the beam have been investigated. Twelve GFRP reinforced concrete (RC) beams were designed, cast and tested. Six GFRP RC beams were tested under static loading to examine the failure modes and associated energy absorption capacities. The remaining six GFRP RC beams were tested under impact loading using a drop hammer machine at the University of Wollongong. GFRP RC beams with higher reinforcement ratio showed higher post cracking bending stiffness and experienced flexural-critical failure under static loading. However, GFRP RC beams under impact loading, regardless of their shear capacity, experienced a "shear plug" type of failure around the impact zone. Energy absorption capacities of beams were determined. The average dynamic amplification factor was calculated as 1.15, indicating higher dynamic moment capacities compared to static moment capacities (15–20% increase). Reinforcement ratio and the strength of concrete influenced the behaviour of GFRP RC beams.